Advocating for a holistic culture of school wellbeing—an evaluation of the Well Schools whole school approach to pupil and teacher wellbeing - Hennessey, Alexandra; MacQuarrie, Sarah; Pert, Kirsty; Mason, Carla; Verity, Lily (Frontiers in Education, 2025)
IntroductionSupporting wellbeing within education settings is vital. Whole school approaches present a holistic and integrated mechanism that recognises school staff, the school community, and pupils. The Well Schools whole school approach to supporting teacher and pupil wellbeing provides a framework that guides planning, policy, and practice while allowing for bespoke and socially valid approaches suitable for each school community.MethodA case study approach explored how schools adopted the Well Schools framework, and what practices and provisions schools were offering as part of Well Schools. Second, it aimed to identify the perceived impact of embedding the Well Schools approach for schools, teachers, and pupils. Ten case study schools were recruited that were implementing Well Schools and that represented diversity in setting type, varying locations across the UK, and school demographics. Data was collected via interviews (n = 16) with school leaders and class teachers that focused on their experiences and engagement with the whole school approach, with particular attention to the process of implementation.FindingsSix themes were identified covering how Well Schools was being implemented, what drove this, and the impact it was having: (1) staff enrichment, (2) pupil enrichment, (3) motivation, (4) capability, (5) awareness and engagement, and (6) sustainability. Findings suggest the value of supporting staff and pupil wellbeing was central to an effective learning environment that supported wellbeing. Well Schools offered the opportunity for schools to build relationships, collaborate, and learn from a network of schools. This network and the engagement with like-minded schools were identified as a reason why some schools were attracted to the whole school approach.ConclusionPromoting Well Schools can help other schools adopt better practices for health, wellbeing, and identify ways of developing holistic wellbeing at the school, teacher, and pupil levels. Such continued engagement further exemplifies the feasibility, acceptability, and positive impact the case study schools reported regarding Well Schools.